PENGEMBANGAN MODEL PELATIHAN BERBASIS KEARIFAN LOKAL DALAM MENINGKATKAN PROFESIONALISME TUTOR PAKET C DI KABUPATEN BONE BOLANGO - Duludu, Ummyssalam A.T.A (2012)
The problem underlying this research is the fact that tutor training at package C is still conventional in implementation. This is evident in the low tutor competencies and also the training outcomes which have not yet been implemented in package C learning activities. One of the efforts taken to address this problem is by developing the training model based on the local wisdom to enhance the professionalism of tutors of package C. This research aims to develop a training model based on local wisdom in improving the professionalism of tutors of package C in the district of Bone Bolango. The theories used in this research are: the theory of local wisdom, training management, nonformal education and continuing education (out-of-school education), professionalism, and adult learning. The approach used in this study is qualitative and quantitative approaches. The method used in this study was research and development (R & D) involving the following activities: 1) preliminary study, 2) development of the initial draft model, 3) validation by the expert and revision of the model, 4) implementation of the model, 5) testing the effectiveness of the model, and 6) developing the recommended model. The results of the research about the training based on local wisdom show that; 1) the initial condition of the tutor training package C is still conventional. This can be observed in the activities carried out starting from the planning stage, organization, implementation, assessment and evaluation stages which have not been implemented to their full potential, 2) validation of experts has led to the development of a training model based on local wisdom to enhance the professionalism of tutors of package C, 3) there is no cooperation with the relevant agencies in the monitoring of post-training activities, 4) The training model based on local wisdom developed in this study from the analysis and testing of the qualitative and quantative data effectively contributed to the improvement of tutor professionalism of package C. The findings of this research reveal that the training model based on local should recommended to the responsive parties in improving professionalism of tutors of package C such the participants of package C are motivated to participate in the activities. The conclusion from this study indicates that the training model developed based on local wisdom led to the improvement of tutor professionalism of package C in the District of Bone Bolango.